Estudio de factibilidad para la implementación de una almacenadora y secadora de maíz y cacao de las asociaciones de agricultores del recinto santa maría, manga del cura del cantón El Carmen, provincia de Manabí, año 2013 - Cevallos Vera, Fabiola Monserrate (2015)
This project aims to conduct a " FEASIBILITY STUDY FOR THE IMPLEMENTATION OF A DRY AND ALMACENADORA CORN AND COCOA FARMERS ASSOCIATIONS OF PRECINCT SANTA MARIA DEL CURA MANGA " , whose main purpose is to provide the service dried and stored , improving quality and presentation and thus increase the income of small farmers as well as their quality of life. Data collection was performed by applying farmer surveys , comprising catorces the same questions that were distributed in four subjects to study as market research , technical, economic and financial. Were designed and implemented appropriate techniques and methods that once analyzed contributed to hypothesis testing later issue the respective conclusions and recommendations based on the study developed. The project to be feasible as it is set to one of their biggest problems such as storage and drying of maize and cocoa by climate change and not knowing how to store their products and sell when the farmer gets a poor- as having a poor investment.